Analisis Penerapan Elektronik Kesehatan (E-Kes) di Puskesmas Rawat Inap Kota Bengkulu - Deni Triyanto; Soehito Efendi (Universitas Medan Area, 2019)
The purpose of this research is to analyze the application of Health Electronics (E-Kes) on Puskesmas Bengkulu city and what are the obstacles, using a descriptive qualitative research method with indicators from (Indrajit, 2006), namely Support, Capacity and Value. Data collection techniques through interviews, observation and documentation. The informants of this research were stakeholders, policy implementers, Heads, Operators, and the community. The results of the study revealed that the support or support of stakeholders in the implementation of E-Kes had not been maximized such as the socialization support of the implementation of e-Kes not carried out continuously, the capacity available at the Puskesmas has not been able to support the application of E-Kes to the maximum, the Value or benefits felt by the government are very By applying this E-case, the related office can analyze the resource needs in the Puskesmas. The inhibiting factors in the application of E-Kes on Puskesmas Bengkulu City are: Human resources, infrastructure and collaboration between stakeholders. The conclusion that the application of E-Kes on Puskesmas Bengkulu City is not optimal because there are still problems with human resources, infrastructure and weak collaboration between stakeholdersÂ